MicroRNA miR-425 inhibits proliferation and migration of colorectal cancer HCC116 cells - Huifang Zhou; Wen Liu; Haiyun Chen; Jiajia Ni; Zhi Zhang; Aimin Xu (Journal of the Pakistan Medical Association, 2021)
Objective: To verify the role of miR-425 in colorectal carcinogenesis. Methods: We conducted sphere formation assay, wound-healing assay, transwell assay, MTT cell proliferation assay, flow cytometric analysis, reverse transcription qPCR, and Western blotting to analyse proliferation and invasion of HCT116 cells transfected with miR-425 mimics, miR-425 inhibitor, miR-425 mimic negative control, and miR-425 inhibitor negative control, respectively. The experimental protocol was approved by the Medical Ethics Committee of the First People’s Hospital in Kashi (approval number: 2018 Kuaishen No. (100)). All experiments were conducted during December 2016 to July 2017 at Xinjiang Dingju Medical Laboratory, China. Results: Our results showed that miR-425 expression in HCT116 cells after transfection was up-regulated, which inhibited sphere formation. Overexpression of miR-425 inhibited proliferation of HTC116 cells and induced their apoptosis, and inhibited HCC116 cell migration and invasion. Conclusion: Overexpression of miR-425 could inhibited sphere formation, the migration and invasion of HCT116 cells through inhibiting proliferation and promoting apoptosis. Keywords: apoptosis; colonic carcinoma; microRNA; proliferation Continuous....